Rancang Bangun Sistem Informasi Inventarisasi dan Peminjaman Peralatan Laboratorium - Solekhan, Solekhan; Dahlan, Muhammad; Susanto, Arief; Cahyo Wibowo, Budi; Indira Asri, Vikha (Jurnal Teknologi, Fakultas Teknik, Universitas AKPRIND Indonesia, 2023)
A laboratory is a building or a room where scientific experiments, analyses, and research are carried out. Muria Kudus University has several laboratories which are used by lecturers and students to carry out several activities including learning, practicums, trials, and other lecture activities. Apart from being a place for practical activities, the laboratory is also used as a place to store various practical equipment and materials that require inventory. The process of borrowing practicum tools and materials has become a routine activity for practitioners who will carry out practicum activities. In the process of borrowing tools and materials in the Muria Kudus University laboratory, conventional methods are still used, namely by writing in a borrowed book or on borrowed paper. Apart from that, the inventory of laboratory equipment and practical materials is also not well documented because conventional methods are still used in the inventory process of laboratory equipment and materials. The research focuses on designing and creating an information system for inventory and borrowing tools and materials in the Muria Kudus University laboratory. This research discusses how to provide facilities to laboratory assistants in managing laboratory assets digitally and make it easier for students or lecturers to carry out practical activities in the laboratory. This management system is web-based and created using the PHP, JavaScript and MySQL programming languages as the database.